(untitled) (Mustansiria Dental Journal, 2018)
There is controversy as to which instrumentation &/or obturation techniques to choose with which type of sealer give better apical sealing. This in vitro study aimed to evaluate the apical sealing ability of three obturation techniques and two types of sealer. A total of 120 teeth were randomly divided into two groups; roots prepared using step-back and hybrid techniques. Each group of instrumented roots were subdivided randomly into three obturation groups of 20 roots for each; each one of these obturation techniques were used twice; once with ZOE sealer and other with AH26 sealer. Then dye penetration study conducted & samples were examined under the stereomicroscope. Data had been collected from two independent examiners and statistically analyzed using student t-test. Concerning the obturation techniques, warm vertical compaction showed best apical sealing. Regarding sealers, AH 26 sealer had better sealing ability than ZOE sealer with highly significant difference. Warm vertical compaction obturation technique in combination with the AH 26 resin sealer obturates the canals with lesser apical leakage.